The Mjølnir impact event and its consequences geology and geophysics of a late jurassic/early cretaceous marine impact event - Dypvik, Henning; Tsikalas, Filippos; Smelror, Morten (New York Springer, 2010)
The Mjølnir impact structure was recognized in 1993 and included in the Earth Impact Database in 1996, based on the discoveries of unequivocal meteorite impact indicators such as shocked quartz, Ir-enrichments, possible glass remnants, fragments of nickel-rich iron oxides, in addition to the convincing complex crater shape of the structure. This book presents the geological and geophysical history of the Barents Sea region along with the discovery of the Mjølnir impact crater. We place the Mjølnir event into the geological framework of the region and present elaborative numerical models of its formation and associated tsunami generation. The book represents an update and synthesis as well as the complete compilation of the Mjølnir crater stu
Introduction -- Geological Framework -- Impact Structure and Morphology -- Impact Geophysics and Modeling -- Impact Cratering and Postimpact Sedimentation -- Ejecta Geology -- The Impact Dynamics -- Structural Analysis of Deformed Central Peak Sediments -- Post-impact Deformation due to Sediment loang -- The Mjølnir Tsunami
"With 166 figures, 74 in color."
Electronic reproduction.
Keywords: Impact craters; Submarine geology; Crate industry